The April 30th, 2006, Mt. Vezzi landslides (Ischia Island, Italy) in the context of the sliding susceptibility of volcanic soils in Campania - Iovino, Michele; Perriello Zampelli, Sebastiano (Italian journal of engineering geology and environment, 2007)
In this paper some of the main features of the landslides that occurred on April 30th, 2006, on the northern slope of M.Vezzi, on the Ischia island (province of Naples, southern Italy), are described. Such landslides represent a further example of volcanic debris slides - avalanches - flows in Campania. Although occurred in a particular geological and geomorphological context, due to the unique nature and landscape of the Ischia island in Campania, they share with other similar landslides in the region the fact of having developed within volcanic soils that derive from the alteration of thin formations of pyroclastic sediments. Having ascertained that they originated near to discontinuities in the volcanic soil cover, as is observed for the majority of the landslides of the same type in Campania, a study aimed at the verification of the possibility of the spatial predictability of their initial sliding areas has been carried out. Within such study, two different data sets have been analyzed, with the same methodological approach. The former data set is represented by the information that was available before April 30th, 2006, while the latter has integrated it with a new representation of the northern slope of M.Vezzi, performed combining ground-based photogrammetry techniques with GPS surveying. It resulted that the used method can provide an effective screening of the sliding susceptibility in volcanic soils; in addition, that the method can greatly take advantage of enhancements to the ground surface representation, with respect to what is typically provided by aerophotogrammetric maps. In particular, such enhancements can help in identifying, either directly or by means of the curvature of the ground surface, the discontinuities within volcanic soil covers. The study lies in the framework of searching, in advance of likely landslides, the zones where “active”, local and targeted soil cover stabilization would be desirable; to begin, for example, with slopes above very vulnerable foothill areas.